New Mutations Causing the Premature Termination of Translation in the A Subunit Gene of Coagulation Factor XIII - Kangsadalampai, Sasichai; Farges-Berth, Anne; Hande Çaglayan, S; Board, Philip G (Thrombosis and Haemostasis, 1996)
The amplification of factor XIIIA subunit gene exons and heteroduplex analysis has been used to identify two new mutations that cause severe factor XIII deficiency. One mutation in a family of French origin results from a 4 bp deletion and leads to a premature termination of translation. The other mutation occurred in a Turkish family and results from a C → T transition that inserts a premature translation stop signal at codon 400. Both mutations alter restriction enzyme sites and can be readily detected in amplified exon DNA for genetic counselling or prenatal diagnosis. The new mutations reflect the extensive molecular heterogeneity of factor XIII deficiency.